Copper-Catalyzed Enantioselective Coupling between Allylboronates and Phosphates Using a Phenol–Carbene Chiral Ligand: Asymmetric Synthesis of Chiral Branched 1,5-Dienes - Yasuda, Yuto; Ohmiya, Hirohisa; Sawamura, Masaya (Synthesis, 2018)
Details of the Cu-catalyzed enantioselective allyl–allyl coupling reaction between allylboronates and (Z)-allylic phosphates using a new chiral N-heterocyclic carbene (NHC) ligand containing a phenolic hydroxy group are presented. The copper catalysis delivers enantioenriched chiral 1,5-dienes with a tertiary stereogenic center. Compatibility with various functional groups and the use of earth-abundant and relatively low-toxicity copper as a metal are attractive features of this protocol. The utility of the chiral phenol–NHC ligand for enantioselective copper catalysis with organoboron compounds is demonstrated and enantiodiscrimination models are discussed.
Keywords: asymmetric catalysis; allylic substitution; synthetic methods copper catalysis; organoboron compounds